Heterogeneous-element-doped zinc sulfide (Mn-ZnS (at) NC) negative electrode material anchored on bowknot-shaped carbon plate and preparation method thereof

Through simple hydrothermal reaction and low-temperature vulcanization technology, zinc sulfide (Mn-ZnS@NC) anode material doped with heterogeneous elements anchored on bow-shaped carbon sheets was prepared, solving the problems of volume changes and poor conductivity of the negative electrode materials of existing lithium-ion batteries, and achieving high capacity and long-life lithium-ion batteries.

CN119822399APending Publication Date: 2025-04-15EAST CHINA UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510073786.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing lithium-ion battery anode materials such as zinc sulfide, such as poor alkaline ion storage performance due to volume changes and poor conductivity, is difficult to meet the needs of high capacity and long life.

Method used

A combination of simple hydrothermal reaction and low-temperature vulcanization technology was used to prepare zinc sulfide (Mn-ZnS@NC) anode material doped with heterogeneous elements anchored on bow-shaped carbon sheets. The method includes synthesizing a bow-shaped MOF precursor, low temperature vulcanization and carbon coating to form an electrode material with excellent conductivity and high content of heterogeneous elements doping.

Benefits of technology

The high capacity and long life performance of lithium-ion batteries are achieved, and the high charge and discharge capacity can be maintained after 1,000 cycles, and the cycle stability of the battery is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822399A_ABST
    Figure CN119822399A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery negative electrode materials, in particular to a method for preparing a hetero-element doped zinc sulfide (Mn-ZnS at NC) negative electrode anchored on a bowknot-shaped carbon plate by combining a simple hydrothermal reaction and a low-temperature vulcanization technology, and a lithium ion battery with high capacity and long service life. The negative electrode material is prepared from the following raw materials: trimesic acid, polyvinylpyrrolidone, zinc nitrate hexahydrate, manganese nitrate tetrahydrate, powdered sulfur, dopamine hydrochloride and trihydroxymethyl aminomethane. According to the negative electrode material, a bowknot-shaped metal organic ligand MOF precursor is synthesized through a simple hydrothermal method, then hetero-element-doped zinc sulfide is obtained through a low-temperature vulcanization technology, and finally carbon coating is carried out through dopamine hydrochloride coating and annealing technologies. And finally, the hetero-element doped zinc sulfide (Mn-ZnS-NC) negative electrode anchored on the bowknot-shaped carbon plate is obtained, and the lithium ion battery has the performance of high capacity and long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials for lithium-ion batteries, and in particular to a method for preparing a zinc sulfide (Mn-ZnS@NC) negative electrode doped with heteroelement and anchored on a bow-knot-shaped carbon sheet by combining a simple hydrothermal reaction with a low-temperature sulfurization technology, and a lithium-ion battery with high capacity and long life. Background Art

[0002] Due to the objective existence of energy crisis in today's society, reliable energy storage devices are indispensable. They play a vital role in helping humans to rationally utilize the earth's energy and enjoy a more comfortable life. Lithium-ion batteries are currently the main energy storage devices for portable electronic devices and electric vehicles.

[0003] In order to meet the growing demand for energy storage capacity and cycle stability in electric vehicles and large-scale energy storage devices, researchers are constantly exploring high theoretical capacity anode materials to replace commercial graphite. Transition metal oxides and sulfides are strong candidates for anode materials due to their high theoretical capacity, low cost and environmental friendliness. For example, zinc sulfide has a high theoretical capacity (973 mAh g−1). However, its alkaline ion storage performance is severely limited due to its severe volume change and inherent poor conductivity during charge and discharge.

[0004] In recent years, heteroatom doping is considered to be an effective way to improve the performance of zinc oxide / zinc sulfide electrode materials. There is also a heterogeneous structure between zinc oxide and zinc sulfide, coupled with the synergistic effect between multiple metals, which can effectively improve the electrochemical properties of zinc oxide and zinc sulfide. To this end, the present invention provides a method for preparing a heteroelement-doped zinc sulfide (Mn-ZnS@NC) negative electrode anchored on a bow-tie-shaped carbon sheet by combining a simple hydrothermal reaction with a low-temperature sulfurization technology, which has high capacity and long life lithium-ion battery performance. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a zinc sulfide (Mn-ZnS@NC) negative electrode doped with heteroelements and anchored on a bow-tie-shaped carbon sheet by combining a simple hydrothermal reaction with a low-temperature sulfurization technology, and a high-capacity, long-life lithium-ion battery performance. The lithium-ion battery negative electrode material of the present invention can effectively improve electronic conductivity, increase active sites, and control volume expansion, so that the lithium-ion battery has excellent charge and discharge capacity and good long-cycle stability.

[0006] The purpose of the present invention is to provide a method for preparing a zinc sulfide (Mn-ZnS@NC) negative electrode doped with heteroelements and anchored on a bow-knot-shaped carbon sheet by combining a simple hydrothermal reaction with a low-temperature vulcanization technology, and a high-capacity, long-life lithium-ion battery performance, comprising the following steps: a) synthesizing a bow-knot-shaped MOF precursor by a simple hydrothermal method, using anhydrous ethanol and N,N-dimethylformamide mixed solution as a solvent, trimesic acid as an organic ligand, polyvinyl pyrrolidone as a template, hexahydrated zinc nitrate, and tetrahydrated manganese nitrate as a metal ion source, and synthesizing a bow-knot-shaped MOF material by a hydrothermal method. b) performing low-temperature vulcanization by a CVD chemical vapor deposition method, using sulfur powder as a sulfur source, placing 5 times the sulfur powder of the MOF precursor upstream of a tube furnace, and placing the MOF downstream, and heating and keeping warm in an Ar gas atmosphere for low-temperature vulcanization. c) The Mn-ZnS material was carbon-coated, dopamine was used as the carbon source, deionized water was used as the solvent, tris(hydroxymethyl)aminomethane) was used as the oxidant, equal amounts of dopamine hydrochloride and the sample were added, the coating was synthesized by stirring at room temperature, the material was centrifuged for washing and drying, and annealing was performed in an Ar atmosphere to obtain Mn-ZnS@NC.

[0007] Preferably, the volume ratio of the anhydrous ethanol and N,N-dimethylformamide mixed solution is 1:1, the amount of PVP used as the template is 1.5 g, the amount of trimesic acid is 315 mg, the amount of zinc nitrate hexahydrate is 223 mg, and the amount of manganese nitrate tetrahydrate is 95 mg.

[0008] Preferably, the hydrothermal temperature for the MOF synthesis is 160° C., and the insulation time is 7 hours.

[0009] Preferably, the temperature of the CVD sulfurization treatment is 350°C, the temperature is kept for 3 hours, and the heating rate is 2°C*min -1 .

[0010] Preferably, the concentration of tris(hydroxymethyl)aminomethane is 1.24 g*L -1 , stirring time is 2 hours.

[0011] Preferably, the carbon coating annealing temperature is 600 ° C, the temperature is kept for 2 hours, and the heating rate is 5 ° C * min -1 .

[0012] A method for preparing heteroelement-doped zinc sulfide anchored on bow-tie-shaped carbon sheets (Mn-ZnS@NC) anode and high-capacity, long-life lithium-ion battery performance by combining a simple hydrothermal reaction with a low-temperature sulfurization technique.

[0013] A method for preparing a zinc sulfide (Mn-ZnS@NC) negative electrode doped with heteroelements and anchored on a bow-knot-shaped carbon sheet by combining a simple hydrothermal reaction with a low-temperature sulfurization technology, and a high-capacity, long-life lithium-ion battery performance. The method includes the following steps: a) synthesizing a bow-knot-shaped MOF precursor by a simple hydrothermal method, using anhydrous ethanol and N,N-dimethylformamide mixed solution as a solvent, trimesic acid as an organic ligand, polyvinyl pyrrolidone as a template, hexahydrated zinc nitrate, and tetrahydrated manganese nitrate as metal ion sources, and synthesizing a bow-knot-shaped MOF material by a hydrothermal method. b) performing low-temperature sulfurization by CVD chemical vapor deposition, using sulfur powder as a sulfur source, placing 5 times the sulfur powder of the MOF precursor upstream of a tube furnace, and placing the MOF downstream, and heating and keeping warm in an Ar gas atmosphere for low-temperature sulfurization. c) Carbon coating of Mn-ZnS material, dopamine as carbon source, deionized water as solvent, tris(hydroxymethyl)aminomethane as oxidant, adding equal amount of dopamine hydrochloride and sample, stirring at room temperature to synthesize coating, centrifugal washing and drying, annealing treatment in Ar atmosphere, and obtaining Mn-ZnS@NC. The Mn-ZnS@NC electrode of the present invention is a bow-tie-shaped nitrogen-doped carbon sheet as a skeleton, and carbon-coated manganese-doped ZnS particles are anchored on the surface, and have excellent conductivity and high content of impurity element doping. Experiments show that the cycle performance of the lithium-ion battery assembled with the Mn-ZnS@NC electrode in the present invention at a current density of 0.5 A / g can still maintain a capacity of 977 mAh / g after 1000 cycles, and charge and discharge at a high current density of 2A / g, and the specific capacity is stably maintained at 616 mAh / g after 1000 cycles, with high capacity and excellent stability. Compared with the prior art, the process flow of the present invention is advanced, environmentally friendly and easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Of course, the drawings in the following description are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0015] Figure 1 This is the XRD diagram of the negative electrode material in Example 1 of the present invention.

[0016] Figure 2 This is the Raman graph of the negative electrode material in Example 1 of the present invention.

[0017] Figure 3 This is the XPS graph of the negative electrode material in Example 1 of the present invention.

[0018] Figure 4This is a SEM image of the final sample of the negative electrode material in Example 1 of the present invention.

[0019] Figure 5 This is the charge and discharge cycle curve of the lithium ion battery of Example 1 of the present invention at a current density of 0.5 A / g.

[0020] Figure 6 This is the charge and discharge cycle curve of the lithium ion battery of Example 1 of the present invention at a current density of 2.0 A / g. DETAILED DESCRIPTION

[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] The present invention provides a method for preparing a heteroelement-doped zinc sulfide (Mn-ZnS@NC) negative electrode anchored on a bow-knot-shaped carbon sheet by combining a simple hydrothermal reaction with a low-temperature sulfurization technology, and a lithium-ion battery with high capacity and long life, comprising the following steps: a) synthesizing a bow-knot-shaped MOF precursor by a simple hydrothermal method, using a mixed solution of anhydrous ethanol and N,N-dimethylformamide as a solvent, trimesic acid as an organic ligand, polyvinyl pyrrolidone as a template, zinc nitrate hexahydrate, and manganese nitrate tetrahydrate as metal ion sources, and synthesizing a bow-knot-shaped MOF material by a hydrothermal method.

[0023] b) Low-temperature sulfurization is performed by CVD chemical vapor deposition, using sulfur powder as the sulfur source. The sulfur powder, which is 5 times the amount of the MOF precursor, is placed upstream of the tube furnace, and the MOF is placed downstream. In an Ar gas atmosphere, heating and insulation are performed for low-temperature sulfurization.

[0024] c) The Mn-ZnS material was carbon-coated, dopamine was used as the carbon source, deionized water was used as the solvent, tris(hydroxymethyl)aminomethane) was used as the oxidant, equal amounts of dopamine hydrochloride and the sample were added, the coating was synthesized by stirring at room temperature, the material was centrifuged for washing and drying, and annealing was performed in an Ar atmosphere to obtain Mn-ZnS@NC.

[0025] The Mn-ZnS@NC electrode of the present invention is based on a bow-tie-shaped nitrogen-doped carbon sheet as the skeleton, and carbon-coated manganese-doped ZnS particles are anchored on the surface, and have excellent conductivity and high content of impurity element doping. Experiments show that the cycle performance of the lithium-ion battery assembled with the Mn-ZnS@NC electrode in the present invention at a current density of 0.5 A / g can still maintain a capacity of 977 mAh / g after 1000 cycles. When charged and discharged at a high current density of 2 A / g, the specific capacity is stably maintained at 616 mAh / g after 1000 cycles, and has high capacity and excellent stability. Compared with the prior art, the process of the present invention is advanced, environmentally friendly and easy to implement.

[0026] The present invention has no special restrictions on the types of the electrodes, separators and electrolytes. For example, in lithium-ion batteries, the electrodes can be lithium sheets; the separators can be polypropylene separators; and the electrolyte can be 1 M LiPF6+EC / DEC (1:1) v / v mixed solvent mixture. The materials are cut to a suitable size and directly used as electrodes to assemble R2016 button batteries.

[0027] The present invention uses a current density of 2 A / g to carry out a constant current charge and discharge experiment at room temperature to test the cycle performance of the lithium ion battery, and the charge and discharge voltage is limited to 0.01 to 3 V. The CT2001A battery test system of Wuhan Blue Electric Electronics Co., Ltd. is used to test the electrochemical performance of the battery. The results show that the cycle performance of the lithium ion battery in the present invention at a current density of 0.5 A / g can still maintain a capacity of 977 mAh / g after 1000 cycles. When charged and discharged at a high current density of 2A / g, the specific capacity is stably maintained at 616 mAh / g after 1000 cycles, and has good cycle stability and high capacity.

[0028] To further illustrate the present invention, the following detailed description is given of a method for preparing a miscellaneous element-doped zinc sulfide (Mn-ZnS@NC) negative electrode anchored on a bow-tie-shaped carbon sheet by combining a simple hydrothermal reaction with a low-temperature sulfurization technology, and the performance of a lithium-ion battery with high capacity and long life, in conjunction with the embodiments provided by the present invention. However, it should not be construed as limiting the scope of protection of the present invention.

[0029] Example 1

[0030] The bow-tie MOF precursor was synthesized by a simple hydrothermal reaction method. 60 ml of a 1:1 volume ratio of anhydrous ethanol and N,N-dimethylformamide mixed solution was used as the solvent, 1.5 g of PVP was added as the template, 315 mg of trimesic acid was used as the organic ligand, 223 mg of zinc nitrate hexahydrate, and 95 mg of manganese nitrate tetrahydrate was used as the metal source. The precursor was placed in a polytetrafluoroethylene reactor at 160 ° C for 7 hours, and after cooling to room temperature, it was washed with anhydrous ethanol and centrifuged, and vacuum dried at 80 ° C for 24 hours to prepare the precursor. The precursor was placed in the downstream of the tube furnace for low-temperature heat treatment, and 1:5 sulfur powder was placed in the upstream of the tube furnace. The temperature was raised to 350 ° C at a rate of 2 ° C / min and kept warm for 3 h. Mn-ZnS was obtained by a one-step gas phase sulfurization method. With a concentration of 1.24 g*L in 100 ml, the precursor was prepared by a one-step gas phase sulfurization method. -1 The tris(hydroxymethyl)aminomethane) aqueous solution was used as solvent, and an equal amount of dopamine hydrochloride and sample were added, stirred at room temperature for 2 hours, washed with deionized water, centrifuged, and dried at 80 °C in vacuum. Under Ar atmosphere, the heating rate was 5 °C*min -1 , the temperature was raised to 600 °C and kept at this temperature for 2 hours to obtain a composite material of zinc sulfide (Mn-ZnS@NC) doped with heteroelements and anchored on bow-knot-shaped carbon sheets prepared by combining simple hydrothermal reaction with low-temperature sulfurization technology. The XRD spectrum of Mn-ZnS@NC is shown in Figure 1 As shown, according to the peak intensity comparison of the characteristic peaks and the comparison with the standard card, it is concluded that it is a mixture of hexagonal and cubic ZnS. The strong diffraction peaks at around 26°, 28° and 30° are the 100, 002 and 101 diffraction peaks of the hexagonal ZnS, and the strong diffraction peak at around 28° is the 111 diffraction peak of the cubic ZnS. Figure 2 This is the Raman spectrum of Mn-ZnS@NC. The intensity ratio of D peak to G peak is 1.01. Figure 3 This is the XPS overall spectrum of Mn-ZnS@NC. Figure 4 This is the SEM morphology of Mn-ZnS@NC. According to SEM, it can be concluded that the zinc sulfide composite material anchored on the bow-knot-shaped carbon sheet was successfully synthesized. Figure 5 The Mn-ZnS@NC assembled lithium-ion battery has excellent cycling performance at a current density of 0.5 A / g, and can still maintain a capacity of 977 mAh / g after 1000 cycles. Figure 6 The cycling performance of the lithium-ion battery assembled with Mn-ZnS@NC is that at a current density of 0.5 A / g, the capacity can still be maintained at 977 mAh / g after 1000 cycles. The cycling performance at a current density of 2.0 A / g is that the capacity can still be maintained at 616 mAh / g after 1000 cycles, showing high capacity and good cycling stability.

[0031] Example 2

[0032] The bow-tie MOF precursor was synthesized by a simple hydrothermal reaction method. 60 ml of a 1:1 volume ratio of anhydrous ethanol and N,N-dimethylformamide mixed solution was used as the solvent. No gPVP was added as a template agent. The amount of trimesic acid was 315 mg as an organic ligand, the amount of zinc nitrate hexahydrate was 223 mg, and the amount of manganese nitrate tetrahydrate was 95 mg as a metal source. It was placed in a polytetrafluoroethylene reactor at 160 ° C for 7 hours. After cooling to room temperature, it was washed with anhydrous ethanol and centrifuged. It was vacuum dried at 80 ° C for 24 hours to prepare the precursor. The precursor was placed in the downstream of the tube furnace for low-temperature heat treatment, and 1:5 sulfur powder was placed in the upstream of the tube furnace. The temperature was raised to 350 ° C at a rate of 2 ° C / min and kept warm for 3 h. Mn-ZnS was obtained by a one-step gas phase sulfurization method. With a concentration of 1.24 g*L in 100 ml -1 The tris(hydroxymethyl)aminomethane) aqueous solution was used as solvent, and an equal amount of dopamine hydrochloride and sample were added, stirred at room temperature for 2 hours, washed with deionized water, centrifuged, and dried at 80 °C in vacuum. Under Ar atmosphere, the heating rate was 5 °C*min -1 , the temperature was raised to 600 ℃ and kept for 2 hours to obtain a zinc sulfide (Mn-ZnS@NC) composite material doped with miscellaneous elements prepared by combining simple hydrothermal reaction with low-temperature sulfurization technology.

[0033] Example 3

[0034] The bow-tie MOF precursor was synthesized by a simple hydrothermal reaction method. 60 ml of a 1:1 volume ratio of anhydrous ethanol and N,N-dimethylformamide mixed solution was used as the solvent, 1.5 g of PVP was added as the template, 315 mg of trimesic acid was used as the organic ligand, 223 mg of zinc nitrate hexahydrate, and 64 mg of manganese nitrate tetrahydrate was used as the metal source. The precursor was placed in a polytetrafluoroethylene reactor at 160 ° C for 7 hours, and after cooling to room temperature, it was washed with anhydrous ethanol and centrifuged, and vacuum dried at 80 ° C for 24 hours to prepare the precursor. The precursor was placed in the downstream of the tube furnace for low-temperature heat treatment, and 1:5 sulfur powder was placed in the upstream of the tube furnace. The temperature was raised to 350 ° C at a rate of 2 ° C / min and kept for 3 h. Mn-ZnS was obtained by a one-step gas phase sulfurization method. With a concentration of 1.24 g*L in 100 ml, the precursor was prepared by a one-step gas phase sulfurization method. -1 The tris(hydroxymethyl)aminomethane) aqueous solution was used as solvent, and an equal amount of dopamine hydrochloride and sample were added, stirred at room temperature for 2 hours, washed with deionized water, centrifuged, and dried at 80 °C in vacuum. Under Ar atmosphere, the heating rate was 5 °C*min -1 , the temperature was raised to 600 ℃ and kept warm for 2 hours to obtain a zinc sulfide (Mn-ZnS@NC) composite material doped with miscellaneous elements prepared by combining a simple hydrothermal reaction with a low-temperature sulfurization technology.

[0035] Example 4

[0036] The bow-tie MOF precursor was synthesized by a simple hydrothermal reaction method. 60 ml of a 1:1 volume ratio of anhydrous ethanol and N,N-dimethylformamide mixed solution was used as the solvent, 1.5 g of PVP was added as the template, 315 mg of trimesic acid was used as the organic ligand, 223 mg of zinc nitrate hexahydrate, and 32 mg of manganese nitrate tetrahydrate was used as the metal source. The precursor was placed in a polytetrafluoroethylene reactor at 160 ° C for 7 hours, and after cooling to room temperature, it was washed with anhydrous ethanol and centrifuged, and vacuum dried at 80 ° C for 24 hours to prepare the precursor. The precursor was placed in the downstream of the tube furnace for low-temperature heat treatment, and 1:5 sulfur powder was placed in the upstream of the tube furnace. The temperature was raised to 350 ° C at a rate of 2 ° C / min and kept for 3 h. Mn-ZnS was obtained by a one-step gas phase sulfurization method. With a concentration of 1.24 g*L in 100 ml, the precursor was prepared by a one-step gas phase sulfurization method. -1 The tris(hydroxymethyl)aminomethane) aqueous solution was used as solvent, and an equal amount of dopamine hydrochloride and sample were added, stirred at room temperature for 2 hours, washed with deionized water, centrifuged, and dried at 80 °C in vacuum. Under Ar atmosphere, the heating rate was 5 °C*min -1 , the temperature was raised to 600 ℃ and kept for 2 hours to obtain a zinc sulfide (Mn-ZnS@NC) composite material doped with miscellaneous elements prepared by combining simple hydrothermal reaction with low-temperature sulfurization technology.

[0037] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a zinc sulfide (Mn-ZnS@NC) negative electrode doped with heteroelement and anchored on a bow-tie-shaped carbon sheet by combining a simple hydrothermal reaction with a low-temperature sulfurization technique and a high-capacity, long-life lithium-ion battery performance. The method comprises the following steps: a) A bow-tie-shaped MOF precursor was synthesized by a simple hydrothermal method, using a mixed solution of anhydrous ethanol and N,N-dimethylformamide as a solvent, trimesic acid as an organic ligand, polyvinyl pyrrolidone as a template, zinc nitrate hexahydrate and manganese nitrate tetrahydrate as metal ion sources, and a bow-tie-shaped MOF material was synthesized by a hydrothermal method; b) low-temperature sulfurization is performed by CVD chemical vapor deposition, using sulfur powder as the sulfur source, placing 5 times the sulfur powder of the MOF precursor upstream of the tube furnace, and placing the MOF downstream, and heating and keeping warm in an Ar gas atmosphere for low-temperature sulfurization; c) The Mn-ZnS material was carbon-coated, dopamine was used as the carbon source, deionized water was used as the solvent, tris(hydroxymethyl)aminomethane) was used as the oxidant, equal amounts of dopamine hydrochloride and the sample were added, the coating was synthesized by stirring at room temperature, the material was centrifuged for washing and drying, and annealing was performed in an Ar atmosphere to obtain Mn-ZnS@NC.

2. The method according to claim 1, characterized in that In step (a), the volume ratio of the mixed solution of anhydrous ethanol and N,N-dimethylformamide is 1:1, the amount of PVP used as a template is 1.5 g, the amount of trimesic acid is 315 mg, the amount of zinc nitrate hexahydrate is 223 mg, and the amount of manganese nitrate tetrahydrate is 95 mg.

3. The preparation method according to claim 1, characterized in that: In step (a), the hydrothermal temperature is 160° C. and the insulation time is 7 hours.

4. The preparation method according to claim 1, characterized in that: The temperature of the CVD treatment in step (b) is 350°C, kept at this temperature for 3 hours, and the heating rate is 2°C*min -1 .

5. The preparation method according to claim 1, characterized in that: The concentration of tris(hydroxymethyl)aminomethane in step (c) is 1.24 g*L -1 , stirring time is 2 hours.

6. The preparation according to claim 1, characterized in that In step (c), the annealing temperature is 600 °C, the temperature is kept for 2 hours, and the heating rate is 5 °C*min -1 .

7. A method for preparing a zinc sulfide (Mn-ZnS@NC) negative electrode doped with heteroelement and anchored on a bow-tie-shaped carbon sheet by combining a simple hydrothermal reaction with a low-temperature sulfurization technique and a high-capacity, long-life lithium-ion battery performance, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 6.